Raised by God for a Life with God: Thinking Theologically About the Resurrection of the Body - Hill, Daniel Lee (Pro ecclesia, 2024)
While it has become somewhat commonplace to lament the lack of attention eschatology has received in the modern era, the interest this area of Christian doctrine does receive often seems to be in service of present existential and ethical concerns. This article lays the foundation for a theology of the resurrection of the body. In it, I argue that theological reflection on the resurrection of the body must be grounded in distinctively theological premises that are integrated within the overarching fabric of Christian doctrine. Building on the work of the late John Webster, this author argues that dogmatic reflection on the resurrection of the body must focus on it as a species of the self-communicative action of the Triune God ad extra and the effects of that action wherein God works to secure a people of his own possession who might love and worship him.